The Effect of Extreme Rainfall Events on Riverbank Slope Behaviour - Nazrien Ng, Jeffery; Mohd Taib, Aizat; Razali, Irfan Haziq; Abd Rahman, Norinah; Wan Mohtar, Wan Hanna Melini; A. Karim, Othman; Mat Desa, Safari; Awang, Suriyani; Mohd, Mohd Syazwan Faisal (Frontiers in Environmental Science, 2022)
Many slope failures take place during or after rainfall events. Landslides are one of the tragedies associated with slope failures and often lead to fatal accidents. A study on the effects of extreme rainfall on slope stability considering the historical rainfall data, slope characteristics and properties, and flow boundary conditions was undertaken. This study investigated the behaviour of the Sg Langat slope under the influence of extreme rainfall gathered from historical data. Sg Langat was selected as the research area because of its high riverbank failures. The focus of this study are as follows: (i) to determine the effect of slope angles on slope stability, (ii) to assess the development of pore-water pressure based on the changing groundwater levels, and (iii) to analyse the influence of extreme rainfall events on the slope behaviour via numerical modelling. This study enhances the understanding of certain slope conditions and contributes to the analysis of slope stability through numerical modelling, making it relatively convenient to observe the soil conditions for determining the slope stability of the research area in regards to the effect of extreme rainfall. The results were obtained with respect to the changes in the pore-water pressure and the factor of safety. It was observed that the pressure changes were different for every channel, demonstrating that the generation of negative pore-water pressure was not directly affected by the type of analysis and the rainfall infiltration alone. Moreover, the slopes on all channels presented were considered unstable because of the considerable changes in the negative pore-water pressure at a relatively shallow depth, causing soil strength reduction. The factor of safety recorded for Channel 1 was the lowest at 0.18, whereas Channel 3 had the highest factor of safety of 1.11 but was still considered unsafe as it fell below the standard safety margin of 1.3. Apart from the different rainfall intensities applied, the geometry of the slopes also affected the slope stability.